CHANGES IN THE FIELD OF CONTINUOUS EDUCATION - Zokirova Mohidilhon Suvankhanovna, Abdukodirova Ziroathon Solidzhonovna, Ibragimova Mashkhura Zakirovna, Zakirov Abdurakhmon son of Vosid (Journals Park Publishing, 2023)
The article highlights the priority areas of state policy in the field of education and upbringing of a harmoniously developed generation. About big changes in the field of continuous education, and about further improvement of the system of postgraduate education.
Keywords: Quality education, personality formation, postgraduate education